PENGARUH SOSIALISASI QRIS, LITERASI DIGITAL DAN EFISIENSI TERHADAP PENGGUNAAN UANG ELEKTRONIK SISWA SMP NEGERI 3 MUARA BUNGO - Pratiwi, Ananda Intan (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2025)
The purpose of this study was to assess how the socialization of QRIS, digital literacy, and efficiency influence the use of electronic money among junior high school students at SMP Negeri 3 Muara Bungo. The context for this research stems from the increasing number of digital transactions among adolescents, which is not matched by an adequate understanding of financial technologies like QRIS. This study uses a quantitative approach with a survey method to test the research hypotheses, involving 86 respondents proportionally selected from grades VII, VIII, and IX. Data analysis was performed using several statistical tests, including instrument tests and hypothesis testing, aided by SPSS version 25. The research findings indicate that the three independent variables—QRIS socialization, digital literacy, and efficiency—have a positive and significant influence, both individually and collectively, on students’ use of electronic money. These three factors are proven to play a crucial role in enhancing students’ interest and ability to use electronic money wisely, safely, and efficiently. This research contributes to the development of digital financial literacy at the secondary school level and serves as a foundation for educational policies that support the integration of financial technologies in the school environment.